Hydrogen: A brief overview on its sources, production and environmental impact - Baykara, Sema Z. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
A brief overview is presented involving the terms of availability of hydrogen, its properties and possible sources and its production methods, and finally, its relationship with renewable energy utilisation, environment and climate. Solar hydrogen, preferably obtained from water, is confirmed once more to be the most environment and climate compatible (causing the least damage), energy source; though not necessarily the most economic one. Production cost of hydrogen obtained from terrestrial biomass, is not the lowest either, however carbon-neutral feature of terrestrial biomass renders it highly desirable in view of steep rise in global temperature. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Hydrogen sources; Hydrogen production; Climate change; LIFE-CYCLE ASSESSMENT; SYNGAS PRODUCTION; SOLAR HYDROGEN; BIOHYDROGEN PRODUCTION; STEAM GASIFICATION; PRODUCTION OPTIONS; PARTIAL OXIDATION; RENEWABLE ENERGY; GAS-PRODUCTION; FOSSIL-FUELS; Chemistry; Electrochemistry; Energy & Fuels